My Poyln - Marcel Herbst (European Journal of Life Writing, 2020)
The note of My Poyln was written as an introduction to a planned photography book regarding a Jewish past that is cleansed from its erstwhile meaning, desolated, and mourned. The thrust to research and photograph a former time grew slowly, over many years. My reading of the Holocaust is one of grief about the denial of the past (and a more humane future) and the lost cross-ethnic, rich culture. That theme I follow in writing and photography—next to my more normal concerns relating to more mundane matters—see: www.4mat.ch.